THE IMPACT OF TEMPERATURE ON FURAN RESIN AND BINDER STRUCTURE (Metallurgy and Foundry Engineering, 2012)
Exposure to high temperature causes a series of structural changes in binders used to prepare moulding and core sands. These changes may consist in the formation of new bonds, changes to their character or a transformation of the structure which may be accompanied, for example, by the destruction (disappearance) of some chemical bonds. They have a significant impact on the mechanical and technological properties of sands, but also on their environmental noxiousness or the ability to reclaim the sand. This article presents the results of infrared structural examinations of two furan resins and two binders produced based on those resins. Both pure resins and binders made of them were exposed to temperature. Changes taking place in their structure in the 25-200 °C temperature range were determined using infrared spectroscopy.